Experimental investigation of convective heat transfer for night cooling with diffuse ceiling ventilation. (15th April 2021) - Guo, Rui; Heiselberg, Per; Hu, Yue; Johra, Hicham; Zhang, Chen; Jensen, Rasmus Lund; Jønsson, Kim Trangbæk; Peng, Pei
Abstract: The convective heat transfer coefficient (CHTC) is a crucial parameter for night ventilation performance estimation. This paper investigates the heat transfer of night ventilation with diffuse ceiling ventilation (DCV) concept in an office room. A series of dynamic full-scale experiments were conducted with different thermal mass distribution schemes, air change rates per hour (ACH), and supply temperatures. The CHTC at interior surfaces with the inlet and outlet temperatures as the reference and the temperature efficiency of DCV were then derived. In most cases, the experimental CHTCs differed significantly from the CHTCs predicted by existing correlations. The presence of furniture (tables), its location, and the thermal mass installed on the walls had little influence on the CHTC at the floor. However, increasing the thermal mass of one surface can significantly augment its own surface CHTC. New correlations based on experimental CHTCs were developed for potential application in building energy simulation tools. The temperature efficiency of DCV decreased with the increase of ACH, the initial temperature difference between the supply air and indoor air, and the thermal mass level. DCV had higher temperature efficiency than the mixing ventilation and displacement ventilation, except for the case with displacement ventilation at low ACH. Highlights: Conduct dynamic experiments for heat transfer of diffuse ceiling ventilation. Compare the deduced convective heat transfer coefficient with correlations in literatures. Develop correlations of convective heat transfer coefficient for night cooling. Study the impact of thermal mass, airflow, and inlet temperature on heat transfer. Study the temperature efficiency for surface cooling of diffuse ceiling ventilation.